2022
DOI: 10.3390/biomedicines10061288
|View full text |Cite
|
Sign up to set email alerts
|

Primary Biliary Cholangitis and Primary Sclerosing Cholangitis: Current Knowledge of Pathogenesis and Therapeutics

Abstract: Cholangiopathies encompass various biliary diseases affecting the biliary epithelium, resulting in cholestasis, inflammation, fibrosis, and ultimately liver cirrhosis. Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are the most important progressive cholangiopathies in adults. Much research has broadened the scope of disease biology to genetic risk, epigenetic changes, dysregulated mucosal immunity, altered biliary epithelial cell function, and dysbiosis, all of which interact and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 252 publications
(295 reference statements)
3
30
0
Order By: Relevance
“…Among them, gut microbes modify BAs metabolism to generate unconjugated BAs and secondary BAs via microbial enzymes, including bacterial bile salt hydrolase (BSH) enzymes, bacterial stereospecific hydroxysteroid dehydrogenases (HSDH), and 7α-dehydroxylase. , Coincidentally, as the differential bacteria between the GOS supplement with the LPS challenge group and the LPS challenge group, Lactobacillus was reported to exhibit a high BSH enzyme activity, which suggested that the GOS supplement with LPS challenge group had a stronger deconjugation ability to conjugate BAs than that of the LPS challenge group. More specifically, Lactobacillus , Veillonella , Streptococcus , and unclassified Lactobacillales , as harmless or even beneficial bacteria, have been reported that their abundances are positively correlated with the level of CDCA or UCDA. , In the present study, the abundances of these bacteria were increased in jejunal content of piglets after GOS supplement. However, GOS supplement only prevented the reduction of CDCA induced by LPS challenge but did not significantly prevent the reduction of other BAs.…”
Section: Discussionsupporting
confidence: 54%
“…Among them, gut microbes modify BAs metabolism to generate unconjugated BAs and secondary BAs via microbial enzymes, including bacterial bile salt hydrolase (BSH) enzymes, bacterial stereospecific hydroxysteroid dehydrogenases (HSDH), and 7α-dehydroxylase. , Coincidentally, as the differential bacteria between the GOS supplement with the LPS challenge group and the LPS challenge group, Lactobacillus was reported to exhibit a high BSH enzyme activity, which suggested that the GOS supplement with LPS challenge group had a stronger deconjugation ability to conjugate BAs than that of the LPS challenge group. More specifically, Lactobacillus , Veillonella , Streptococcus , and unclassified Lactobacillales , as harmless or even beneficial bacteria, have been reported that their abundances are positively correlated with the level of CDCA or UCDA. , In the present study, the abundances of these bacteria were increased in jejunal content of piglets after GOS supplement. However, GOS supplement only prevented the reduction of CDCA induced by LPS challenge but did not significantly prevent the reduction of other BAs.…”
Section: Discussionsupporting
confidence: 54%
“…PBC and PSC, the most important progressive and immune-mediated cholangiopathies in adults, are characterized by biliary tract injuries, portal inflammation, sequential fibrosis/cirrhosis development, evolving towards end-stage liver failure [37,38]. In this context, alteration in the expression of tight junction associated proteins (including a downregulation of ZO1 expression) has been described in both PBC (mainly in bile ducts) and PSC (in hepatocytes) [39,40].…”
Section: Tight Junction Disruption As a Consequence Of Cholangiopathies?mentioning
confidence: 99%
“…As reported, PBC may influence the gut microbiome composition through alterations of intestinal motility, immune response, bile acid secretion, as well as portal hypertension development. Antimitochondrial antibodies present in 90–95% of PBC patients, which can occur years before the disease’s onset, react to the pyruvate dehydrogenase complex E2 (PDC-E2) expressed by the biliary epithelium [ 150 , 151 ]. Several reports showed that the synthesis of antibodies against bacterial proteins as well as the molecular mimicry of microbial proteins and PDC-E2 are critical for PBC development [ 152 , 153 , 154 , 155 ].…”
Section: Dysbiosis In Immune-related Cholangiopathiesmentioning
confidence: 99%